DISTINCTIVE FEATURES IN SEMANTICS AND WORD FORMATION - Zebuniso Ramazonova (Journals Park Publishing, 2024)
The purpose of the research is to study and determine the peculiar features of anthroponyms, to define semantic aspects, ways of their formation, culture-specific characteristics. It also suggests varied classifications comparing different languages. This study used descriptive-analytic, comparative method, semantic analysis, partially componential analysis methods.
Keywords: anthroponyms, proper names, word formation, affixation. abbreviation, blending.